Access to generic antiretrovirals: inequality, intellectual property law, and international trade agreements Acceso a antirretrovirales genéricos: desigualdad, derecho de propiedad intelectual y acuerdos comerciales internacionales - Arachu Castro; Michael Westerhaus (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
The governments of numerous low- and middle-income countries are currently instituting rules that strengthen changes in domestic intellectual property legislation, often made to conform to the mandates of "free" trade agreements signed with the United States. These measures frequently include intellectual property provisions that extend beyond the patent law standards agreed upon in recent World Trade Organization negotiations, which promised to balance the exigencies of public health and patent holders. In this paper, we analyze the concern that this augmentation of patent law standards will curtail access to essential medicines, particularly as they relate to the AIDS pandemic. We critically examine the potential threats posed by trade agreements vis-à-vis efforts to provide universal access to antiretroviral medications and contend that the conditioning of economic development upon the strengthening of intellectual property law demands careful attention when public health is at stake. Finally, we examine advocacy successes in challenging patent law and conclude that greater advocacy and policy strategies are needed to ensure the protection of global health in trade negotiations. Actualmente diversos países de renta media y baja están creando leyes de propiedad intelectual más rígidas, muchas veces para adaptarse a las exigencias de los tratados de "libre" comercio con los Estados Unidos. Tales medidas suelen incluir dispositivos que transcienden las normas sobre patentes negociadas recientemente en la Organización Mundial del Comercio, que prometían equilibrar las exigencias de la salud pública y las de patentes. Este artículo analiza la preocupación de que este endurecimiento restrinja el acceso a medicamentos esenciales, en particular en el contexto de la pandemia de SIDA. El artículo examina las amenazas potenciales creadas por los tratados comerciales contra los esfuerzos dirigidos para el acceso universal a los antirretrovirales, manteniendo que condicionar el desarrollo económico al endurecimiento de la legislación requiere una atención escrupulosamente justificada cuando la salud pública está en juego. Finalmente, se examinan algunos éxitos obtenidos por grupos de presión, concluyéndose que son necesarias más estrategias políticas y de presión para garantizar la protección de la salud mundial en las negociaciones sobre tratados internacionales de comercio.